1987
DOI: 10.1002/hup.470020308
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of temazepam versus nitrazepam on memory and vigilance in the normal subject

Abstract: Eighteen normal volunteers with no sleep difficulties were given psychological tests and asked to fill out a self-evaluation questionnaire 11 h after administration of a hypnotic drug, nitrazepam 5 rng or temazepam 20 mg (in the form of soft gelatin capsules), which was compared to a placebo. Subjects received all three treatments at 1-week intervals, with the administration sequence determined by drawing lots. The tests used were the images test, the digitlsymbol substitution test (DSST), choice reaction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Meta-analysis confirmed that nitrazepam 10 mg is likely to impair performance the entire day after bedtime administration and experts rated the effects initially as severe and declining to moderate (Berghaus, 1998;Wolschrijn et al, 1991). Nitrazepam 5 mg was occasionally found to produce significant residual impairment between 8 and 12 hours after the administration (e.g., Bourin et al, 1987;Godtlibsen et al, 1986;Laurell and Tornros, 1986;Morgan, 1985;Subhan and Hindmarch, 1984a), but not on performance in the driving test (Volkerts and O'Hanlon, 1986). There was no consensus among experts with respect to the severity of residual effects of nitrazepam 5 mg.…”
Section: Long Half-life Hypnoticsmentioning
confidence: 99%
“…Meta-analysis confirmed that nitrazepam 10 mg is likely to impair performance the entire day after bedtime administration and experts rated the effects initially as severe and declining to moderate (Berghaus, 1998;Wolschrijn et al, 1991). Nitrazepam 5 mg was occasionally found to produce significant residual impairment between 8 and 12 hours after the administration (e.g., Bourin et al, 1987;Godtlibsen et al, 1986;Laurell and Tornros, 1986;Morgan, 1985;Subhan and Hindmarch, 1984a), but not on performance in the driving test (Volkerts and O'Hanlon, 1986). There was no consensus among experts with respect to the severity of residual effects of nitrazepam 5 mg.…”
Section: Long Half-life Hypnoticsmentioning
confidence: 99%